1995
DOI: 10.1093/geront/35.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Nursing Home Residents' Participation in Activity Programs

Abstract: Nursing homes are mandated by the Omnibus Budget Reconciliation Act (OBRA) to provide activity programs (U.S. Congress, 1987). Little information exists, however, as to residents' participation in activity programs. Using data from a Health Care Financing Administration project, the present study examines the relationship between resident characteristics and time participating in activities. Among 2,672 nursing home residents we found measures of resource use, cognitive abilities, depression, sense of initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 0 publications
2
37
1
Order By: Relevance
“…Finally, some of the association between obesity and television viewing could reflect confounding. For example, patients with mental health symptoms may spend more time watching television 12,20,21 and are at increased risk for obesity. [22][23][24] Obesity is a major health problem among women who receive care through the Department of Veterans Affairs (VA) and affects approximately 30%.…”
mentioning
confidence: 99%
“…Finally, some of the association between obesity and television viewing could reflect confounding. For example, patients with mental health symptoms may spend more time watching television 12,20,21 and are at increased risk for obesity. [22][23][24] Obesity is a major health problem among women who receive care through the Department of Veterans Affairs (VA) and affects approximately 30%.…”
mentioning
confidence: 99%
“…Most studies show that especially residents with dementia rarely do anything (Perrin , 1997 ;Kolanowski et al , 2006 ;Hill et al , 2010 ); when they are not in bed during the daytime they sleep 30 % of the time (Schnelle et al , 1998 ). By contrast, one study observed more participation in activities in residents with mild to moderate dementia compared to those without dementia, possibly due to their required engagement in rehabilitation (Voelkl et al , 1995 ). These residents spend most of their activity time in therapeutic activities (Chung , 2004 ), but this amount becomes less when they have severe dementia (Voelkl et al , 1995 ;Buettner and Fitzsimmons , 2003 ;Chung , 2004 ;Kolanowski et al , 2006 ).…”
Section: Physical Inactivitymentioning
confidence: 90%
“…By contrast, one study observed more participation in activities in residents with mild to moderate dementia compared to those without dementia, possibly due to their required engagement in rehabilitation (Voelkl et al , 1995 ). These residents spend most of their activity time in therapeutic activities (Chung , 2004 ), but this amount becomes less when they have severe dementia (Voelkl et al , 1995 ;Buettner and Fitzsimmons , 2003 ;Chung , 2004 ;Kolanowski et al , 2006 ).…”
Section: Physical Inactivitymentioning
confidence: 90%
See 2 more Smart Citations